Study of Clean and Healthy Living Behavior on Fishers at Fish Auction Places Oeba, Fatubesi Sub-District, Kota Lama District, Kupang City in 2020 - Indah Haeru Nisa; Apris Adu; Sigit Purnawan (Universitas Nusa Cendana, 2022)
A clean and Healthy Lifestyle is one of the effective ways to prevent and control the risk of transmission among fishers. However, poor implementation of clean and healthy living behavior is still found in Fish Auction Places, especially on fishing boats. This study aims to describe the behavior of clean and healthy living on fishers in the Oeba Fish Auction Place. The indicators of clean and healthy living behavior include smoking behavior, using clean water, washing hands using soap before eating and after defecating, using latrines, and using personal protective equipment. This research is a qualitative descriptive study with five informants consisting of two ship owners and three crew members. Data collection was carried out using in-depth interviews and observations around the fish auction vessel. The results showed that of the five indicators, one indicator had been implemented well by fishermen, namely the behavior of using clean water. The lack of support from stakeholders and awareness of fishers has worsened the implementation of clean and healthy behavior at the Oeba Fish Auction Place. So, the implementation of clean and healthy living behavior at the Fish Auction Place had not been implemented optimally on all indicators. Therefore, education about the importance of maintaining health and the risk of disease transmission in the surrounding environment and the provision of supporting factors such as facilities and infrastructure is indispensable for implementing clean and healthy living to achieve a healthy degree. Keywords: fishers, clean and healthy lifestyle, fish auction place